Parasites in brains of wild rodents (Arvicolinae and Murinae) in the city of Leipzig, Germany. (December 2019) - Waindok, Patrick; Özbakış-Beceriklisoy, Gökben; Janecek-Erfurth, Elisabeth; Springer, Andrea; Pfeffer, Martin; Leschnik, Michael; Strube, Christina
Abstract: Small rodents serve as intermediate or paratenic hosts for a variety of parasites and may participate in the transmission of these parasites into synanthropic cycles. Parasites with neuroinvasive stages, such as Toxoplasma gondii or Toxocara canis, can cause detrimental damage in the brain of intermediate or paratenic hosts. Therefore, the occurrence of neuroinvasive parasite stages was evaluated in brains of wild rodents captured in the city of Leipzig, Germany. In addition, a few specimens from the cities of Hanover, Germany, and Vienna, Austria were included, resulting in a total of 716 rodents collected between 2011 and 2016. Brains were investigated for parasitic stages by microscopic examination of native tissue, artificially digested tissue as well as Giemsa-stained digestion solution to verify positive results. Infective stages of zoonotic ascarids or other helminths were not detected in any sample, while coccidian cysts were found in 10.1% (95% CI: 7.9–12.5%; 72/716) of examined brains. The most abundant rodent species in the study was the bank vole ( Myodes glareolus ; Arvicolinae), showing an infection rate with cerebral cysts of 13.9% (95% CI: 11.0–17.8%; 62/445), while 2.7% (95% CI: 1.0–5.8%; 6/222) of yellow-necked mice ( Apodemus flavicollis ; Murinae) were infected. Generalized linear modelling revealed a statistically significant difference in prevalence between M. glareolus and A. flavicollis, significant local differences as well as an effect of increasing body mass on cyst prevalence. Coccidian cysts were differentiated by amplification of the 18S rRNA gene and subsequent sequencing. The majority of identifiable cysts (97.9%) were determined as Frenkelia glareoli, a coccidian species mainly circulating between M. glareolus as intermediate and buzzards ( Buteo spp.) as definitive hosts. The zoonotic pathogen Toxoplasma gondii was confirmed in one M. glareolus originating from the city of Leipzig. Overall, it can be concluded that neuroinvasion of zoonotic parasites seems to be rare in M. glareolus and A. flavicollis . Graphical abstract: Image 1 Highlights: In examined rodents, neuroinvasion of zoonotic parasites seems to be rare. The coccidia Frenkelia glareoli was the most abundant neuroinvasive parasite. The zoonotic pathogen Toxoplasma gondii was identified in one Myodes glareolus brain. No neuroinvasive zoonotic helminth stages were detected in the rodents' brains.